Becoming neighbors with refugees and voting for the far-right? The impact of refugee inflows at the small-scale level - Melinda Fremerey; Lukas Hörnig; Sandra Schaffner (RWI - Leibniz-Institut für Wirtschaftsforschung, 2022)
We investigate the effect of the refugee inflow between 2014 and 2017 on voting for the far-right party Alternative for Germany (AfD) in the national parliamentary election in 2017 in Germany. Drawing on unique small-scale data enables us to distinguish between the contact theory, captured by the inflow of refugees into the immediate neighborhood (1km x 1km), and county-level (NUTS 3) effects, which might pick-up other, broader factors such as media coverage or specific county-level policies. We alleviate concerns of an endogenous refugee allocation by a shift-share instrument. Our results indicate that the contact theory is valid in urban West Germany, i. e., higher refugee inflows in West German urban neighborhoods decrease the shares of far-right voting, while there is no robust evidence of a relationship between refugee inflow and far-right vote shares in East Germany and rural West Germany. – – Wir analysieren die Auswirkungen der Zuwanderung von Geflüchteten zwischen 2014 und 2017 auf das Wahlergebnis der rechtspopulistischen Partei Alternative für Deutschland (AfD) bei der Bundestagswahl 2017. Die Verwendung einzigartiger, kleinräumiger Daten ermöglicht es uns, zwischen Auswirkungen des direkten Kontakts, d.h. des Zustroms von Flüchtlingen in die unmittelbare Nachbarschaft (1km x 1km), und Effekten auf Kreisebene (NUTS 3), welche andere, umfassendere Faktoren wie die Medienberichterstattung oder Lokalpolitik aufgreifen könnten, zu unterscheiden. Einer möglichen endogenen Wohnortentscheidung der Geflüchteten wird durch ein Shift-Share-Instrument Rechnung getragen. Unsere Ergebnisse deuten darauf hin, dass die Kontakttheorie im urbanen Raum in Westdeutschland zutrifft, d.h. dass ein höherer Zustrom von Geflüchteten in westdeutschen Stadtvierteln den Anteil der rechtspopulistischen Wählerschaft senkt, während wir keine robusten Hinweise auf einen Zusammenhang zwischen dem Zustrom von Geflüchteten und rechtspopulistischen Wähleranteilen in Ostdeutschland und im ländlichen Westdeutschland finden.
Keywords: D72; J15; R23; 330; voting behavior; neighborhood characteristics; refugees; immigration